Prevalence, subtypes, severity and determinants of ocular trauma: The Singapore Chinese Eye Study. Issue 2 (16th June 2017) - Wong, Mark YZ; Man, Ryan EK; Gupta, Preeti; Sabanayagam, Charumathi; Wong, Tien Yin; Cheng, Ching-Yu; Lamoureux, Ecosse Luc
Abstract : Purpose: To describe the prevalence, subtypes, severity and determinants of ocular trauma (OT) in a population-based study in Singapore. Methods: We included 3353 Chinese adults aged ≥40 years from the Singapore Chinese Eye Study, a population-based study, conducted between 2009 and 2011. OT was defined as self-reported history of any eye injury requiring medical attention with or without hospitalisation, and further classified as blunt object, sharp object or chemical burns related. Age and gender-standardised prevalence was estimated using the 2010 Singapore Chinese population census. Multivariable models were used to assess the independent associations of OT with age, gender, income, education, literacy, alcohol consumption, smoking and history of falls. Results: The mean (SD) age was 59.7 (9.9) years and 49.4% were male. There were 138 OT cases, giving a crude and age and gender-standardised prevalence of 4.1% (95% CI 3.5% to 4.8%) and 4.4% (95% CI 3.7% to 5.2%), respectively. Of these, 45 (32.6%), 56 (40.6%) and 10 (7.3%) were blunt object, sharp object and chemical burns-related trauma, respectively. Twenty eight (20.3%) required hospitalisation, with no difference between subtypes. In multivariable models, men (OR (95% CI): 2.80 (1.79–4.39)), younger persons (per year decrease in age (1.03 (1.00–1.05)) and lower education levels (1.8 (1.25–2.60); comparing ≤6 years vs >6 years of education) were independent determinants of OT. Conclusions: OT affected one in 25 adults, with 20% of these requiring hospitalisation. Because OT is preventable, raising awareness and education strategies in the population would allow prevention of vision loss particularly in men, and younger and lesser-educated individuals.